The Influence of Distribution, Utilization of Zakat, Infaq, and Sadaqah (ZIS), and Religiosity on the Behavior of Mustahiq and Transparency as an Intervening Variable in Zakat Management Institutions in Tulungagung Regency - Agung Budiman; Akhyak Akhyak; Binti Nur Asiyah (Indonesian Economic Review, 2025)
This research was motivated by the many problems regarding transparency, service and religiosity that occurred in the National Zakat Agency Tulungagung Regency, such as the management of the Tulungagung National Zakat Agency experienced a vacuum in management and in conducting its audits it was not consistent every quarter but only at the end of each year.  This study uses a quantitative approach. The type of research used in this study is associative research. The data collection technique used in this study uses a questionnaire. The population in this study were all Mustahiq at the Tulungagung Zakat Collection Institution, totaling 2166 Mustahiq. Based on the determination of the number of Isaac and Michael samples from a population of 2166, the research sample was 241 respondents, but due to reasons of the suitability of filling out the complete questionnaire, 185 respondents filled out the questionnaire, so that in this study the sample taken was 185 respondents. So the sample in this study was 185 Mustahiq. The results of the study indicate that there is a significant influence of the distribution of Zakat, Infaq and Alms Funds on the behavior of Mustahiq at the Zakat Amil Institution in Tulungagung Regency; There is a significant influence of the utilization of Zakat, Infaq and Alms Funds on the behavior of Mustahiq at the Amil Zakat Institution in Tulungagung Regency; There is a significant influence of religiosity on the behavior of Mustahiq at the Amil Zakat Institution in Tulungagung Regency; There is a significant influence of transparency on the behavior of Mustahiq at the Amil Zakat Institution in Tulungagung Regency; There is no significant influence of the distribution of Zakat, Infaq and Alms Funds on the behavior of Mustahiq through transparency at the Amil Zakat Institution in Tulungagung Regency; There is an influence of the utilization of Zakat, Infaq and Alms Funds on the behavior of Mustahiq through transparency at the Amil Zakat Institution in Tulungagung Regency; There is an influence of religiosity on the behavior of Mustahiq through transparency at the Amil Zakat Institution in Tulungagung Regency.